A novel air injection scheme to achieve MILD combustion in a can-type gas turbine combustor. (1st March 2020) - Sharma, Saurabh; Chowdhury, Arindrajit; Kumar, Sudarshan
Abstract: This article presents the design and development of a can-type gas turbine combustor operating in flameless combustion mode with liquid fuels. The combustor operates with kerosene and thermal intensities varying from 5.1 to 7.5 MW/m 3 . A novel air-injection scheme is proposed, in which air is supplied from different injection holes namely, swirl air near fuel injection, primary, secondary and dilution air in the downstream. These air injection holes are arranged in a way to help create strong recirculation of hot combustion products leading to increased mixing and dilution of incoming fresh reactants. Direction, orientation and mass fraction of swirl, primary, secondary and dilution air are optimized through a series of reacting flow simulations aimed at maximizing the reactant dilution ratio, a key parameter to achieve flameless combustion. It is observed that if the momentum of the air is increased beyond a critical value, the combustor switches its operation into flameless mode due to increased mixing and dilution of fresh reactants with hot combustion products. Combustion occurs in a well-distributed reaction regime within the combustor volume. Measured NOx emissions are less than 5 ppm and acoustic emissions are significantly reduced during the combustor operation in flameless combustion mode. Highlights: Investigated MILD combustion in a can type gas turbine combustor. A novel air injection scheme is adopted to achieve MILD combustion. Combustor switches to MILD combustion mode due to increased momentum of hot air. Novel air injection scheme results in the establishment of large recirculation zones. Combustor exhibits flat thermal field, low gaseous emissions and low noise level.